2020
DOI: 10.1093/treephys/tpaa173
|View full text |Cite
|
Sign up to set email alerts
|

Gall- and erineum-forming Eriophyes mites alter photosynthesis and volatile emissions in an infection severity-dependent manner in broad-leaved trees Alnus glutinosa and Tilia cordata

Abstract: Highly host-specific eriophyoid gall- and erineum-forming mites infest a limited range of broadleaf species, with the mites from the genus Eriophyes particularly widespread on Alnus spp. and Tilia spp. Once infected, the infections can be massive, covering a large part of leaf area and spreading through the plant canopy, but the effects of Eriophyes mite gall formation on the performance of host leaves are poorly understood. We studied the influence of three frequent Eriophyes infections, E. inangulis gall-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…Spreading by the wind is more risky for these organisms because due to the high host specificity of these mites, there is little chance of reaching the appropriate host. On the contrary, having a pollinator of the host plant, the chances for reaching the appropriate host increase as in the case of Aceria litchii Keifer (Acari: Eriophyidae), which is associated with bees that pollinate lychee trees (Jiang et al, 2021) and Aceria pallida Keifer (Acari: Eriophyidae), which is associated with psyllidae Bactericera gobica Loginova (Hemiptera: Triozidae) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spreading by the wind is more risky for these organisms because due to the high host specificity of these mites, there is little chance of reaching the appropriate host. On the contrary, having a pollinator of the host plant, the chances for reaching the appropriate host increase as in the case of Aceria litchii Keifer (Acari: Eriophyidae), which is associated with bees that pollinate lychee trees (Jiang et al, 2021) and Aceria pallida Keifer (Acari: Eriophyidae), which is associated with psyllidae Bactericera gobica Loginova (Hemiptera: Triozidae) .…”
Section: Resultsmentioning
confidence: 99%
“…The practical value of the study lies in the fact that the information on A. platynotus presence, abundance, and spread will help in sampling the mites and making future management decisions Keywords: four-legged mites; identification; varieties; spread; harmfulness; population not cause damage visible to the naked eye, but in case of mass reproduction may lead to rusting, bronzing, or chlorotic appearance of damaged parts. A relatively limited proportion, approximately 10-15% of these mites, reside in natural storage sites on the host or within the galls they create (Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since the content of chlorophylls is directly proportional to the photosynthesis intensity (Lichtenthaler et al 2007;Lambers 2008;Ivanova et al 2018Ivanova et al , 2019Qian et al 2019), the loss of pigments in infected leaves denotes a decrease in the photosynthesis of plants. It has been shown that the net assimilation rate per area and the stomatal conductance strongly decrease with the increasing severity of infestation by Eriophyes gall-forming mites in Alnus glutinosa and Tilia cordata (Jiang et al 2021). The above plant parameters also inversely correlated with the severity of infection by gall wasp species (Jiang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Four-legged mites, or eriophyoids (Acari, Eriophyoidea), are microscopic, highly host-specific phytoparasites, permanently associated with higher vascular plants (Lindquist 1996). Among ≈5,000 known species, about 20% induce various galls, or growth abnormalities, on vegetative and generative plant organs (Skoracka et al 2010;Jiang et al 2021). The genus Eriophyes, which includes about 300 species, is one of the most diverse eriophyoid mite genera (Soika and Kozak 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation